Подготовка Образовательного Процесса К Эпохе Искусственного Интеллекта - Зулунов Равшанбек Маматович (Periodica Journal, 2022)
The introduction of artificial intelligence technologies requires certain preparation from the society. The integration of various smart technologies is a key factor in this era. The article examines the problems of adapting the educational process to new technologies
Keywords: artificial intelligence; big data; cloud computing; Internet of Things